ChemInform Abstract: C2‐Symmetrical Nickel Complexes Derived from α‐Amino Amides as Efficient Catalysts for the Enantioselective Addition of Dialkylzinc Reagents to Aldehydes. Issue 23 (16th May 2013) - Escorihuela, Jorge; Altava, Belen; Burguete, M. Isabel; Luis, Santiago V.
Abstract Aliphatic aldehydes reacting with lower yields and enantioselectivities than the aromatic ones.